Effect of an Acupuncture Technique of Penetrating through Zhibian (BL54) to Shuidao (ST28) with Long Needle for Pain Relief in Patients with Primary Dysmenorrhea: A Randomized Controlled Trial. (18th December 2019) - Wang, Haijun; Cao, Yuxia; Jin, Xiaofei; Yan, Min; Wang, Jianchao; Li, Rangqian; Ji, Laixi
Abstract : Background . Primary dysmenorrhea (PD) is the commonest gynecological disorder in young women of reproductive age, and there is not always satisfactory relief of pain treated by common medications. Therefore, acupuncture has been used as an alternative therapy to relieve the symptoms of PD. In clinical practice, a penetrating method of acupuncture with long needle has been shown to be particularly effective for improving primary dysmenorrhea. This study was conducted to evaluate the effectiveness of this technique for pain relief in patients with primary dysmenorrhea as compared with a conventional pain medication. Methods . The present study is a perspective, randomized, ibuprofen-controlled trial. Sixty-two eligible participants were randomly assigned in a 1 : 1 ratio to receive either acupuncture treatment or ibuprofen administration. The treatment lasted for three menstrual cycles for both groups. The primary outcome was the intensity of menstrual pain measured by using the visual analogue scale at the completion of treatment. Secondary outcomes included the severity of symptoms associated with menstrual pain, responder rate, and safety of acupuncture treatment. The clinical outcomes were measured on each menstrual cycle at baseline, treatment course (3 cycles), and follow-up period. Results . Sixty-four patients of primary dysmenorrhea were recruited, and 62 subjects were included in the final analysis. At trial completion, acupuncture was shown to be associated with a significantly lower pain intensity and decreased symptom severity of primary dysmenorrhea as compared with ibuprofen (p < 0.05 ). A significantly higher responder rate was found in the acupuncture group as compared with the control group (p < 0.05 ). No serious adverse events were reported by patients in either group. Conclusions . The penetrating method of acupuncture with long needle may be an effective and safe therapy for pain relief in patients with primary dysmenorrhea. This trial was registered with the Chinese Clinical Trial Registry (ChiCTR-IOR-17012621 ).